A Comparison of the Caprini Score With an Institutional Risk Assessment Tool for Prediction of Venous Thromboembolism After Total Joint Arthroplasty at an Urban Tertiary Care Health Safety Net Hospital - Brian Gibbs, MD; Samuel Paek, BS; Noelle Wojciechowski, BA; Sean Wrenn, BS; David M. Freccero, MD; Ayesha Abdeen, MD (Arthroplasty Today, 2023)
Background: Patients undergoing total joint arthroplasty (TJA) are at increased risk for venous thromboembolism (VTE). Prediction tools such as the Caprini Risk Assessment Model (RAM) have been developed to identify patients at higher risk. However, studies have reported heterogeneous results when assessing its efficacy for TJA. Patients treated in an urban health safety net hospital have increased medical complexity, advanced degenerative joint disease, and severe disability prior to TJA increasing the risk of VTE. We hypothesize that use of a tool designed to account for these conditions—the Boston Medical Center (BMC) VTE score—will more accurately predict VTE in this patient population. Methods: A retrospective case-control study was performed including subjects 18 years of age and older who underwent primary or revision TJA in an urban academic health safety net hospital. Patients with hemiarthroplasties, simultaneous bilateral TJA, and TJA after acute trauma were excluded. A total of 80 subjects were included: 40 who developed VTE after TJA (VTE+) and 40 who did not develop VTE (controls). Subjects were matched by age, gender, and surgical procedure. Results: There was a statistically significant difference between the mean BMC VTE score for VTE+ and controls (4.40 and 3.13, respectively, P = .036). Conversely, there was no statistical difference between the mean Caprini scores for VTE+ and controls (9.50 and 9.35, respectively, P = .797). Conclusions: In a health safety-net patient population, an institutional RAM—the BMC VTE score—was found to be more predictive of VTE than the modified Caprini RAM following TJA. The BMC-VTE score should be externally validated to confirm its reliability in VTE prediction in similar patient populations.